2014
DOI: 10.1590/s1415-43662014000300009
|View full text |Cite
|
Sign up to set email alerts
|

Manejo da matéria orgânica do solo e estoques de carbono em cultivos de frutas tropicais

Abstract: The main objective of this study was to investigate changes in carbon dynamics and stocks in agricultural soils. Soil samples were collected at 0-10 cm and 10-30 cm depths in two agricultural areas (cultivated with banana (Musa spp.), and cultivated with citrus (Citrus sinensis). A native forest soil was used as a reference and to determine the carbon pool management index. Organic matter was physically fractionated into particulate organic matter (> 53 µm) and complexed organic matter (< 53 µm). Analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
(30 reference statements)
3
9
0
1
Order By: Relevance
“…Firstly, fresh organic matter derived from residues, root secretions, and/or organic fertilizer is often concentrated in the surface layer 36 , leading to a higher POXC in the TL than in the SL (Table 1). Secondly, the differences bwtween R 20 in the TL and the SL may be caused by differences in soil microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, fresh organic matter derived from residues, root secretions, and/or organic fertilizer is often concentrated in the surface layer 36 , leading to a higher POXC in the TL than in the SL (Table 1). Secondly, the differences bwtween R 20 in the TL and the SL may be caused by differences in soil microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Soil tillage leads to degradation of organic matter and causes losses in OC, in spite of the annual deposit of organic residues from the fruit orchards (Bernardi et al, 2007). Evaluating the impact of banana and citrus orchards in relation to native vegetation (remaining from the Atlantic Forest) in the Plateau of Neópolis, Sergipe, Brazil, Guimarães et al, (2014) observed that an irrigated banana plantation resulted in a 14 % increase in the OC content in the and higher c stocks in the heavy and light sOM fraction in comparison to native caatinga, especially in the uppermost soil layer. Many studies have evaluated the SOM dynamic under annual crops in regions with high rainfall (Freixo et al, 2002;Carneiro et al, 2009).…”
Section: Growing Of Mango (Mangifera Indica) Under Irrigated Conditiomentioning
confidence: 99%
“…They observed that the OC stocks were inversely proportional to the depth evaluated. In a study carried out in Sergipe, Brazil, evaluating the impact of eight years of banana growing on the SOM of an Argissolo (Ultisol) in relation to native forest, Guimarães et al (2014) observed that growing irrigated banana resulted in a 14 % increase in the OC content. The greater OC contents found in the area of the banana plantation compared to the native forest area arise from the incorporation of crop residues (leaves and pseudostem) and of the plant material cleared off the area itself, together with the contribution of plant matter from herbaceous species.…”
Section: Organic Carbon Stocksmentioning
confidence: 99%
See 1 more Smart Citation
“…The CMI has been estimated from particle-size fractions (Vieira et al, 2007;Schiavo et al, 2011;Guimarães et al, 2014;Zhao et al, 2014). Recently, Conceição et al (2014) found a high correlation (r = 0.92; p<0.01) between CMI estimated from these fractions and from density fractions (separated with SPT solution).…”
Section: Introductionmentioning
confidence: 99%